(untitled) - 1942-; Johnston, Tony; De Paola, Tomie (New York, 1985)
A pioneer mother lovingly stitches a beautiful quilt which warms and comforts her daughter Abigail; many years later another mother mends and patches it for her little girl.
Keywords: Children's stories, American; Quilts; Fiction; Quilting; Fiction; Mothers and daughters; Fiction